Music, Heart and Soul of Personality: A Pastoral Psychological Reflection - Thannickal, Joseph (Asian Horizons, 2024)
This article explores music as a tool in the formation of Seminarians. As a universal passion, human beings feel the joy and the power of music in their hearts and souls. Needless then to be surprised that the Church has used music in worship for centuries. However liturgical music has not maintained always the same standards of erudition or excellence, as Pope Francis observed in 2017. Hence using music as a formation tool requires watchfulness and updating. The reports in this article are on the author’s heuristic reflections on the experiences of using music in formation. It discusses four areas of a former’s personality where strong influence of music could be beneficial; namely the candidate’s growth as a person, community membership, intercultural competence, and creativity, each with their own subsets of competencies. The Church therefore, would stand to lose if she ignores music’s impact on candidates and seminarians, who would in course of time, assume the roles of Pastoral leadership in the Church. For theology, it will mean another opportunity to explore deeply the interactive space between God’s action and the creative and aesthetic dimensions of the human person where music dwells.